The Influence of Cigarette Advertising on Teenagers' Attitudes Toward Cigarette Purchasing Decisions - Siregar, Ira Nur Dewita (Journal Business Administration: Entrepreneurship and Creative Industry, 2025)
This study aims to analyze the influence of cigarette advertising on adolescents' attitudes toward cigarette purchasing decisions and the role of the media in supporting the cigarette industry. Cigarettes have become a serious issue in global health due to their addictive substances that have a detrimental impact on health. Cigarette advertising, particularly through television and social media, is considered to greatly influence adolescents' perceptions of cigarettes as symbols of “coolness” and masculinity. This study employs a qualitative approach through Focus Group Discussions (FGD) and online media observation. The research findings indicate that most adolescents are unaware of the connection between advertising and their decision to purchase cigarettes; however, advertising still exerts an indirect influence on the formation of adolescents' opinions and attitudes. The study also found that weak government regulations and the widespread presence of cigarette advertisements exacerbate this situation. Therefore, strict oversight of advertisements and cigarette distribution, particularly those targeting teenagers, is crucial in efforts to control cigarette consumption in Indonesia.